2005
DOI: 10.1142/s0217732305017111
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic CMB Sky

Abstract: The ellipticity of the anisotropy spots of the Cosmic Microwave Background measured by the Wilkinson Microwave Anisotropy Probe (WMAP) has been studied. We find an average ellipticity of about 2, confirming with a far larger statistics similar results found first for the COBE-DMR CMB maps, and then for the BOOMERanG CMB maps. There are no preferred directions for the obliquity of the anisotropy spots. The average ellipticity is independent of temperature threshold and is present on scales both smaller and larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…In the present model there are spatial curvature gradients, and we must revisit the calculation from first principles. Volume-average negative spatial curvature, which accords with tests of ellipticity in the CMB anisotropies (Gurzadyan et al 2005(Gurzadyan et al , 2007, can nonetheless be consistent with our local observation of the angular scale of the first peak (Wiltshire 2007a). …”
Section: M0supporting
confidence: 87%
“…In the present model there are spatial curvature gradients, and we must revisit the calculation from first principles. Volume-average negative spatial curvature, which accords with tests of ellipticity in the CMB anisotropies (Gurzadyan et al 2005(Gurzadyan et al , 2007, can nonetheless be consistent with our local observation of the angular scale of the first peak (Wiltshire 2007a). …”
Section: M0supporting
confidence: 87%
“…Previous studies have included non-Gaussianities reported for the CMB properties, such as the multipole alignments, hemisphere anomalies, temperature-independent ellipticity of the excursion sets, large-scale symmetry (see Eriksen et al 2007;Copi et al 2007;Gurzadyan & Torres 1997;Gurzadyan et al 2005Gurzadyan et al , 2007Gurzadyan et al , 2008. Among the signals with low probability at Gaussian fluctuations is a region in the southern sky known as the Cold Spot (Vielva et al 2004;Cruz et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the non-Gaussianities among others reported for CMB properties (e.g. de Oliveira-Costa et al 2004;Copi et al 2007;Schwarz et al 2004;Eriksen et al 2004Eriksen et al , 2007Cruz et al 2005Cruz et al , 2009Gurzadyan et al 2005Gurzadyan et al , 2007Morales & Saez 2008).…”
Section: Introductionmentioning
confidence: 50%